2011
DOI: 10.1258/jms.2011.011027
|View full text |Cite
|
Sign up to set email alerts
|

Minor influence of self-selection bias on the effectiveness of breast cancer screening in case-control studies in the Netherlands

Abstract: Background Self-selection bias is considered to be a problem when evaluating the effectiveness of breast cancer service screening in case-control studies. Objective Using the incidence-based mortality method (IBM), a correction factor for the potential influence of self-selection can be derived from a group of non-screened women and a group of notinvited women. Methods Breast cancer patients, diagnosed in 1990 -1995 and between the ages of 50 to 70, were selected from the Netherlands Cancer Registry and five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…We used individual data on breast cancer mortality in nonparticipants from the study period 1990 to 2003 and, due to privacy regulations, aggregated data on uninvited women from the prescreening period (1986)(1987)(1988)(1989). Our RR of 1.11 was remarkably similar to the RR of 1.08 from another Dutch study (6) that used data on contemporaneous groups of nonparticipants and uninvited women in the implementation period for screening (1990)(1991)(1992)(1993)(1994)(1995) from the same region. If breast cancer mortality after 1990 has been decreasing among nonparticipants (numerator of the RR) due to better treatment, then this would also apply for not invited women (denominator of the RR).…”
supporting
confidence: 82%
“…We used individual data on breast cancer mortality in nonparticipants from the study period 1990 to 2003 and, due to privacy regulations, aggregated data on uninvited women from the prescreening period (1986)(1987)(1988)(1989). Our RR of 1.11 was remarkably similar to the RR of 1.08 from another Dutch study (6) that used data on contemporaneous groups of nonparticipants and uninvited women in the implementation period for screening (1990)(1991)(1992)(1993)(1994)(1995) from the same region. If breast cancer mortality after 1990 has been decreasing among nonparticipants (numerator of the RR) due to better treatment, then this would also apply for not invited women (denominator of the RR).…”
supporting
confidence: 82%
“…these differences could partly be explained by the fact that the trial estimates do not take the pseudo-diagnosis date into account. 10,14 in the current population, the risk in non-attenders appeared to be lower than the risk in uninvited women, which resulted in correction factors smaller than one. the non-attender groups for the case-control and the trial estimates may thus slightly differ.…”
Section: Discussionmentioning
confidence: 67%
“…For the ever/never-estimate, the person-years are therefore based on non-attendance during the entire trial period, which may result in an increased screening opportunity for women who are not diagnosed with breast cancer. 10 in both the trial and the case-control analyses, no marked association between breast cancer screening and breast cancer mortality in women ages 40 to 50 years was observed. Despite the differences, the results from both methods seemed to suggest a similar or smaller breast cancer mortality risk in non-attenders compared with uninvited women.…”
Section: Discussionmentioning
confidence: 75%
“…Given that women with a low SES were more likely to be diagnosed with advanced cancer in this study, we corrected for SES in the multivariable analysis. Furthermore, another study has shown that the overall influence of bias due to self‐selection was minor on the effectiveness of the Netherlands screening program …”
Section: Discussionmentioning
confidence: 99%